In vitro efficacy of synergistic antibiotic combinations in imipenem resistant Pseudomonas aeruginosa strains (Bangladesh Journal of Medical Microbiology, 2017)
The increase in antibiotic resistance coincided with the decline in production of new antibiotics. Combination antibiotic treatment is preferred in nosocomial infections caused by multidrug resistant Pseudomonas aeruginosa. In vitro synergism test by agar dilution method were used to choose the combinations which might be used in clinic. The aim of this study was to investigate the synergistic efficacy of antibiotic combinations in imipenem resistant P. aeruginosa strains. Carbapenem resistance (imipenem and meropenem) wasdetermined by disk diffusion method. Among isolated P. aeruginosa 44.9% were cabapenem resistant. The MIC of drugs among 25 imipenem resistant isolates ranged from >_ 256 mg/L to _ 1024 mg/L to _ 256 mg/L to _ 16 mg/L to _ 512 mg/L to